NAQSHBANDIYA - AS WORLD SCIENCE (Scientific journal of the Fergana State University, 2024)
The article analyzes the role of Khoja Ahrar Vali in the transformation of the Naqshbandi doctrine into a world doctrine. The views of Alisher Navoi on the merits of Khoja Akhror as a famous sheikh, not only in Movarunnahr and Khorasan, but also in Iraq, Azerbaijan, Romania, Egypt, India, Afghanistan and China, are substantiated. Materials are considered that the murids came to Samarkand from Iran, Turkey and India and learned Sufism from Khoja Akhror.